2020
DOI: 10.1371/journal.pone.0230166
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the human serine hydrolase OVCA2 to the model serine hydrolase homolog FSH1 from S. cerevisiae

Abstract: Over 100 metabolic serine hydrolases are present in humans with confirmed functions in metabolism, immune response, and neurotransmission. Among potentially clinically-relevant but uncharacterized human serine hydrolases is OVCA2, a serine hydrolase that has been linked with a variety of cancer-related processes. Herein, we developed a heterologous expression system for OVCA2 and determined the comprehensive substrate specificity of OVCA2 against two ester substrate libraries. Based on this analysis, OVCA2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…37,38 The fluorogenic library is separated into structural groups based on common subclasses of serine hydrolase activity with expansion of the tertiary and bulky esters in the current substrate library (Figure 1). 37,40,45,46 Within these subclasses, the alkyl ester substrates (1−6) allow general classification of serine hydrolases based on substrate length preferences and the introduction of polarity and unsaturation into these substrates (7−11; 12−15) provide greater solubility, reactivity, and selectivity. 38 As a proposed arylesterase with specificity for xenobiotics, 15 LipN may selectively recognize cyclic, hydrophobic, or constrained esters (16)(17)(18)(19)(20)(21)32).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 The fluorogenic library is separated into structural groups based on common subclasses of serine hydrolase activity with expansion of the tertiary and bulky esters in the current substrate library (Figure 1). 37,40,45,46 Within these subclasses, the alkyl ester substrates (1−6) allow general classification of serine hydrolases based on substrate length preferences and the introduction of polarity and unsaturation into these substrates (7−11; 12−15) provide greater solubility, reactivity, and selectivity. 38 As a proposed arylesterase with specificity for xenobiotics, 15 LipN may selectively recognize cyclic, hydrophobic, or constrained esters (16)(17)(18)(19)(20)(21)32).…”
Section: ■ Resultsmentioning
confidence: 99%
“…This pattern of essentiality for the nucleophilic serine and catalytic base histidine and lesser role for the acidic asparate/glutamate residue has been observed in a variety of serine hydrolases and other bHSLs. 40,45,46 Within other conserved bHSL motifs, oxyanion hole residues�Gly 144 and Gly145�were found to be required for complete catalysis, as conservative substitutions with alanine decreased the k cat /K M values by 15-to 140-fold against all three fluorogenic substrates. The only substitution without a near complete loss of catalytic activity was D215A, which had k cat /K M values within 3-fold of wild-type LipN for substrates 1 and 7.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…J. Fungi 2020, 6, x FOR PEER REVIEW 13 of 15 hydrolase fold and employ a Ser-His-Asp catalytic triad [21], but more than half of the serine hydrolases (>120 enzymes) remain poorly annotated, with no described physiological function or identified substrates [19,22]. In this study, the results showed that there was a 10-70% decrease in the four typical yellow pigments by mrpigG deletion.…”
Section: Discussionmentioning
confidence: 66%
“…In current study, the generation of mrpigG mutants by homologous recombination, as shown in Figure 5 and Figure 7 , demonstrated that mrpigG was a member of the MP gene cluster. Searched with the Pfam 33.1 program, the data showed that mrpigG belonged to the serine hydrolase family, which is a large, ubiquitous family of enzymes grouped based on their ability to perform hydrolysis reactions on a range of biological substrates, such as ester, thioester, amide and epoxide bonds in small molecules, peptides or proteins [ 19 , 20 , 21 ]. The majority of serine hydrolases (>60%) adopt an α,β-hydrolase fold and employ a Ser-His-Asp catalytic triad [ 21 ], but more than half of the serine hydrolases (>120 enzymes) remain poorly annotated, with no described physiological function or identified substrates [ 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%